Preserving Human Culture in Schools Through Oral Storytelling: Perspectives From Teachers in Eastern Cape, South Africa - Yamkela Ntwalana; Nomasomi Hilda Matiso (E-Journal of Humanities, Arts and Social Sciences)
With the growth of technology, elderly people in societies no longer gather children to conduct oral storytelling sessions, which are regarded as important tools for the preservation of culture. The objective of this study was to investigate how culture can be preserved through oral storytelling in schools and to determine how oral storytelling can be revived. Vygotsky’s (1978) Sociocultural Theory, which emphasises the importance of social interaction in the construction of social meaning, anchored this inquiry. A qualitative approach, entrenched in an interpretive paradigm, was utilised. An exploratory research design was chosen for this study. Semi-structured interviews were used to gather data from 6 purposely chosen language teachers, that is, 3 grade 9 English Additional Language teachers, and 3 isiXhosa teachers in the Eastern Cape Province, South Africa. Data, which were thematically analysed, indicated that oral storytelling has deteriorated in schools due to curriculum changes, and the influence of the Fourth Industrial Revolution. Multimedia storytelling has replaced oral storytelling. Furthermore, there is a lack of professional development in cultural heritage. The non-practice of oral storytelling could have a negative impact on preserving human culture in schools. The study recommends that culturally literate people from communities, including parents, should be utilised in schools to conduct storytelling sessions to preserve culture. This could be done through the organisation of cultural activities in which learners participate in oral storytelling. By integrating oral storytelling into the educational system, societies can ensure that future generations remain connected to their cultural roots while developing important cognitive and social skills.